2014
DOI: 10.1080/08927014.2014.975797
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of single-walled carbon nanotubes on biofilm formation fromBacillus anthracisspores

Abstract: This study reports the inhibitory effect of single walled carbon nanotubes (SWCNTs) on biofilm formation from Bacillus anthracis spores. Although the presence of 50 to 100 μg ml(-1) of SWCNTs in the suspension increased spore attachment in the wells of 96-well plates, the presence of 200 μg ml(-1) of SWCNTs in the germination solution decreased the germination percentage of the attached spores by 93.14%, completely inhibiting subsequent biofilm formation. The inhibition kinetics of 50 μg ml(-1) SWCNTs on biofi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 65 publications
3
15
0
Order By: Relevance
“…In addition, CNTs have also been viewed as a potential nanofiller with an AF capacity (Beigbeder et al 2008;. Many studies have focused on the AF performance of CNTs on bacteria in laboratory bioassays (Kang et al 2007;Brady-Estévez et al 2008;Huggett et al 2009;Dong & Yang 2014;Yazhini & Prabu 2015). For example, Kang et al (2007) showed CNTs exhibited good efficacy for reducing the viability of Escherichia coli.…”
Section: Settlement Assaymentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, CNTs have also been viewed as a potential nanofiller with an AF capacity (Beigbeder et al 2008;. Many studies have focused on the AF performance of CNTs on bacteria in laboratory bioassays (Kang et al 2007;Brady-Estévez et al 2008;Huggett et al 2009;Dong & Yang 2014;Yazhini & Prabu 2015). For example, Kang et al (2007) showed CNTs exhibited good efficacy for reducing the viability of Escherichia coli.…”
Section: Settlement Assaymentioning
confidence: 97%
“…For example, Kang et al (2007) showed CNTs exhibited good efficacy for reducing the viability of Escherichia coli. Dong and Yang (2014) suggested that CNTs reduced the percentage germination of attached spores of Bacillus anthracis, and prevented the formation of bacterial biofilms. However, knowledge about the interaction between CNTs and natural biofilms in the marine environment is very limited.…”
Section: Settlement Assaymentioning
confidence: 98%
“…32 Long nanotube aggregates in liquid medium are known to be more bioactive and have potent antibiofilm activity, especially during the early phase of biofilm formation. 33 Carbon nanostructures may cause physical abrasions and structural damage to the bacterial cell walls and cell membranes. Graphene sheets can isolate bacteria from the microenvironment which is inimical for survival.…”
Section: Carbon-based Nanomaterialsmentioning
confidence: 99%
“…[169] Due to shorter tube length, the chances of interactions between open ends of nanotubes and microorganism increase, leading to puncturing of the bacterial cell membrane and irreversible cell damage. [172] Among the 2D materials, graphene oxide (GO) and molybdenum disulfide (MoS 2 ) have been intensively used in water remediation application. In a report, after microscopic examinations of coatings containing SWNTs, biofilms of E. coli and B. subtilis at the bottom of the surfaces showed ≈80-90% cell lysis.…”
Section: Wwwadvsustainsyscommentioning
confidence: 99%
“…[171] This, however, is conditional and it is also to be noted that effects are more pronounced only in the early stages of biofilm formation. [172] Among the 2D materials, graphene oxide (GO) and molybdenum disulfide (MoS 2 ) have been intensively used in water remediation application. GO is antibacterial in nature because of its scissoring effect, which results in outer membrane damage into the microbial cells [51,132,173] decreasing bacterial membrane potential due to local perturbation of the cell membrane and, in addition, resulting in leakage of electrolytes.…”
Section: Wwwadvsustainsyscommentioning
confidence: 99%